Board of directors and profitability ratio of Thai non-life insurers - Pongpitch Petchsakulwong (Kasetsart Journal of Social Sciences, 2019)
The aim of this paper was to investigate the impact of board of directors’ characteristics on the profitability ratio of Thai public non-life insurers. Hausman test was employed in the test for the selection between fixed and random effects in our panel data for a sample of 208 firm-years from 2000 to 2012. Return on total assets (ROA), return on equity (ROE), and return on net written premiums (RNP) were used to be proxies for profitability ratio. The findings of our analyses revealed positive and statistically significant results between board size and profitability ratio. On the contrary, board meeting frequency was negative and statistically significant with ROA and RNP. In addition, firm size was negative and statistically significant with profitability ratio.